Red- and Blue-Light Sensing in the Plant Pathogen Alternaria alternata Depends on Phytochrome and the White-Collar Protein LreA - Igbalajobi, Olumuyiwa (mBio, 2019)
The filamentous fungus Alternaria alternata is a common postharvest contaminant of food and feed, and some strains are plant pathogens. Many processes in A. alternata are triggered by light. Interestingly, blue light inhibits sporulation, and red light reverses the effect, suggesting interactions between light-sensing systems. The genome encodes a phytochrome (FphA), a white collar 1 (WC-1) orthologue (LreA), an opsin (NopA), and a cryptochrome (CryA) as putative photoreceptors. Here, we investigated the role of FphA and LreA and the interplay with the high-osmolarity glycerol (HOG) mitogen-activated protein (MAP) kinase pathway. We created loss-of function mutations for fphA, lreA, and hogA using CRISPR-Cas9 technology. Sporulation was reduced in all three mutant strains already in the dark, suggesting functions of the photoreceptors FphA and LreA independent of light perception. Germination of conidia was delayed in red, blue, green, and far-red light. We found that light induction of ccgA (clock-controlled gene in Neurospora crassa and light-induced gene in Aspergillus nidulans) and the catalase gene catA depended on FphA, LreA, and HogA. Light induction of ferA (a putative ferrochelatase gene) and bliC (bli-3, light regulated, unknown function) required LreA and HogA but not FphA. Blue- and green-light stimulation of alternariol formation depended on LreA. A lack of FphA or LreA led to enhanced resistance toward oxidative stress due to the upregulation of catalases and superoxide dismutases. Light activation of FphA resulted in increased phosphorylation and nuclear accumulation of HogA. Our results show that germination, sporulation, and secondary metabolism are light regulated in A. alternata with distinct and overlapping roles of blue- and red-light photosensors.